Austin [large type] - Miller, Linda Lael (Miller, Linda Lael. McKettricks of Texas., 2010)
World champion rodeo star Austin McKettrick finally got bested by an angry bull. His career over, his love life a mess, the lone maverick has nowhere to go when the hospital releases him, except back home to Blue River and the Silver Spur ranch. Austin's overachieving brothers won't allow this cowboy to brood in peace. They've even hired a nurse to speed along his recovery. Paige Remington's bossy brand of TLC is driving him crazy, as is her beautiful face, sexy figure and silky black hair. Paige has lost count of the times Austin has tried to fire her, but this determined nurse is not going anywhere until he's healed, body and heart. Austin's brothers are laying bets that Paige's place in his life just might become permanent.